Water stable isotopes reveal the hydrological response of Costa Rican glacial lakes to climate variability - Esquivel Hernández, Germain (2022)
Lakes are generally considered a key information source for understanding paleoclimate. Here, we use stable water isotopes (δ2H and δ18O) in a high-elevation tropical glacial lake to inform about modern climate variability and local hydrological conditions. We report a data set of water isotopes in precipitation and lake water collected between June 2015 and November 2020 in the Chirripó National Park, Costa Rica. Using a linear resistance model, the isotopic information coupled with lake water temperature and hydrometeorological data allowed the calculation of seasonal evaporation to inflow ratios (E/I) for Lake Ditkevi. Isotopic variations (δ18O and d-excess) reflect seasonal changes in the evaporative conditions, with E/I ratios ranging from 2.7 ± 1.3% to 10.8 ± 5.4%. Significant correlations between lake d-excess, lake water temperature, and sea surface temperature anomalies in El Ni˜no 3.4 region revealed the sensitive hydrological response of this high elevation tropical glacial lake to the cyclic deviations in the ocean-atmosphere domain of warm/cold El Niño Southern Oscillation episodes. Our findings contribute to i) a better understanding of the climatic controls on high-elevation precipitation and surface water systems in the tropics and ii) inform paleoclimate reconstructions in Central America.